2016
DOI: 10.4315/0362-028x.jfp-15-550
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Contamination in Stored Maize and Groundnuts Based on Storage Practices and Conditions in Subhumid Tropical Africa: The Case of Kilosa District, Tanzania

Abstract: Experiments were conducted to assess the influence of storage practices on mycotoxin incidences in stored maize and groundnuts in Kilosa District, Eastern Central Tanzania. Factorial experiments were used to test the effects of processing, storage conditions, and protectants at 3-month intervals for 12 weeks. Temperature and relative humidity data were recorded by using data loggers. The differences among the treatment means were compared using Tukey's honestly significant difference test at 5% probability lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…The included studies that investigated peanuts all reported AFB 1 concentrations in peanuts to be relatively high (> 15 µg/kg set by Codex Alimentarius [hereinafter: “CODEX”]), with only samples from Algeria having a lower mean concentration of 6.3 µg/kg (Magembe, Mwatawala, & Mamiro, 2016a; Magembe, Mwatawala, & Mamiro, 2016b; Magembe, Mwatawala, Mamiro, & Chingonikaya, 2016c; Oyedele et al., 2017; Riba, Matmoura, Mokrane, Mathieu, & Sabaou, 2013). Mean AFB 1 concentrations in African dishes, such as ogiri, kuru‐kuru, and dagwa, were found to be > 5 µg/kg, while AFB 1 concentrations in peanut cake ranged from 13 to 2,824 µg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies that investigated peanuts all reported AFB 1 concentrations in peanuts to be relatively high (> 15 µg/kg set by Codex Alimentarius [hereinafter: “CODEX”]), with only samples from Algeria having a lower mean concentration of 6.3 µg/kg (Magembe, Mwatawala, & Mamiro, 2016a; Magembe, Mwatawala, & Mamiro, 2016b; Magembe, Mwatawala, Mamiro, & Chingonikaya, 2016c; Oyedele et al., 2017; Riba, Matmoura, Mokrane, Mathieu, & Sabaou, 2013). Mean AFB 1 concentrations in African dishes, such as ogiri, kuru‐kuru, and dagwa, were found to be > 5 µg/kg, while AFB 1 concentrations in peanut cake ranged from 13 to 2,824 µg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted to determine afl atoxin contamination in Peanuts in Busia Co-occurrence of Fusarium toxins was also reported with 30 samples or 50% of samples having fumonisins with DON, 10 samples or 17% having DON with HT-2 toxin, 13 samples or 22% having fumonisins with HT-2 toxin, and 2 samples or 3% having DON and ZEN [66].Another study conducted in Kilosa District, Tanzania revealed that maize had fumonisins B 1 contamination ranging from 63.26 ppb to 213.15 ppb. High Afl atoxin contamination was reported in groundnuts ranging from 72.97 ppb to 195.17 ppb which is higher than the 10 ppb limit for EAC countries[23].…”
mentioning
confidence: 75%
“…Afl atoxins and Fumonisins are the most widely spread, detected, and researched mycotoxins occurring in maize and peanuts in the East Africa community region and Africa generally [2,3,12,23]. Afl atoxins B 1 has the highest toxicity among the afl atoxins and accounts for 75% of the total food contamination related to afl atoxins however there is Scanty information available on the prevalence of other mycotoxins like DON, and ZEN in maize and peanuts for human consumption in East Africa though some studies have been undertaken in animal feeds [2,6,18,19,[33][34][35][36][37][38][39][40].…”
Section: Occurrence and Exposure To Mycotoxins In The East African Comentioning
confidence: 99%
See 2 more Smart Citations